Pilot plant ratio control system by using YEWPACK MARK II system / Nur Malek Mohamed Dahari and Mohd Faizal Shaari - Mohamed Dahari, Nur Malek; Shaari, Mohd Faizal (1990)
The advance of low-cost and yet powerful process computer system has made it more convenient now to implement advanced process control to improve control of plant performance and hence plant profitability. Advanced process control techniques are much more sophisticated then the simple PID controllers and thus, it is essential that a correct process simulation based on the knowledge of process dynamic can be developed for control operations and also training purposes.